Moving from assessments to implementation: promising practices for strengthening multisectoral antimicrobial resistance containment capacity - Mohan P. Joshi; Fozo Alombah; Niranjan Konduri; Antoine Ndiaye; Ndinda Kusu; Reuben Kiggundu; Edgar Peter Lusaya; Robert Tuala Tuala; Martha Embrey; Tamara Hafner; Ousmane Traore; Mame Mbaye; et al. (BMC, 2023)
Abstract Background Antimicrobial resistance (AMR) poses a global threat to human, animal, and environmental health. AMR is a technical area in the Global Health Security Agenda initiative which uses the Joint External Evaluation tool to evaluate national AMR containment capacity. This paper describes four promising practices for strengthening national antimicrobial resistance containment capacity based on the experiences of the US Agency for International Development's Medicines, Technologies, and Pharmaceutical Services Program work with 13 countries to implement their national action plans on AMR in the areas of multisectoral coordination, infection prevention and control, and antimicrobial stewardship. Methods We use the World Health Organization (WHO) Benchmarks on International Health Regulations Capacities (2019) to guide national, subnational, and facility actions that advance Joint External Evaluation capacity levels from 1 (no capacity) to 5 (sustainable capacity). Our technical approach is based on scoping visits, baseline Joint External Evaluation scores, benchmarks tool guidance, and country resources and priorities. Results We gleaned four promising practices to achieve AMR containment objectives: (1) implement appropriate actions using the WHO benchmarks tool, which prioritizes actions, making it easier for countries to incrementally increase their Joint External Evaluation capacity from level 1 to 5; (2) integrate AMR into national and global agendas. Ongoing agendas and programs at international, regional, and national levels provide opportunities to mainstream and interlink AMR containment efforts; (3) improve governance through multisectoral coordination on AMR. Strengthening multisectoral bodies' and their technical working groups' governance improved functioning, which led to better engagement with animal/agricultural sectors and a more coordinated COVID-19 pandemic response; and (4) mobilize and diversify funding for AMR containment. Long-term funding from diversified funding streams is vital for advancing and sustaining countries' Joint External Evaluation capacities. Conclusions The Global Health Security Agenda work has provided practical support to countries to frame and conduct AMR containment actions in terms of pandemic preparedness and health security. The WHO benchmarks tool that Global Health Security Agenda uses serves as a standardized organizing framework to prioritize capacity-appropriate AMR containment actions and transfer skills to help operationalize national action plans on AMR.